PERFORMANCE ON MANAGEMENT OF PARLIAMENTARY EXPERTS IN INDONESIA: A MALCOLM BALDRIGE FRAMEWORK ANALYSIS - Putri, Dinda Amalia; Nuh, Mohammad; Wike, Wike (Faculty of Administrative Science, Universitas Brawijaya, 2025)
This study investigates the performance management of parliamentary experts (Tenaga Ahli Anggota Anggota) supporting members of the Indonesian House of Representatives (DPR RI) through the lens of the Malcolm Baldrige Performance Excellence Framework. As non-permanent staff appointed to assist with legislative, budgetary, and oversight functions, parliamentary experts play a pivotal role in enhancing institutional effectiveness. However, fragmented recruitment practices, unstandardized evaluation mechanisms, and limited competency development have led to significant variations in performance quality.Employing a qualitative descriptive approach, this research draws on document analysis, in-depth interviews with parliamentary experts across multiple factions, and field observations. The findings reveal that while the leadership and strategic dimensions of the Baldrige framework are present in varying degrees, critical gaps remain in workforce engagement, performance measurement, and results integration. The study identifies the absence of competency-based recruitment, lack of continuous training, and decentralised performance control as key barriers to achieving high performance.This paper offers a strategic recommendation for adopting an integrated performance management system aligned with Baldrige principles, encompassing clear KPIs, unified evaluation standards, and structured capacity-building programs. By embedding quality management practices, the Indonesian legislative body can strengthen its internal support system and improve the overall quality of parliamentary governance.